2006
DOI: 10.1007/bf02705243
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin-proteasome system

Abstract: The 2004 Nobel Prize in chemistry for the discovery of protein ubiquitination has led to the recognition of cellular proteolysis as a central area of research in biology. Eukaryotic proteins targeted for degradation by this pathway are first 'tagged' by multimers of a protein known as ubiquitin and are later proteolyzed by a giant enzyme known as the proteasome. This article recounts the key observations that led to the discovery of ubiquitin-proteasome system (UPS). In addition, different aspects of proteasom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
409
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 581 publications
(420 citation statements)
references
References 155 publications
6
409
0
5
Order By: Relevance
“…Although no specific UBE2C inhibitors are currently available for clinical use, proteasome inhibitors form a novel class of chemotherapeutic agents that lead to cell cycle arrest and cell death. Bortezomib is a specific reversible inhibitor of proteasome function that is crucial for protein degradation 17 and has been approved by the US Food and Drug Administration for therapy for multiple myeloma. 18 Earlier studies by other groups, including our laboratory, have shown that SCF-SKP2 ubiquitin proteasome pathway alterations in tumors is a ubiquitous phenomenon and is present in various tumors, such as CRC, ovarian carcinomas, and diffuse large Bcell lymphomas.…”
mentioning
confidence: 99%
“…Although no specific UBE2C inhibitors are currently available for clinical use, proteasome inhibitors form a novel class of chemotherapeutic agents that lead to cell cycle arrest and cell death. Bortezomib is a specific reversible inhibitor of proteasome function that is crucial for protein degradation 17 and has been approved by the US Food and Drug Administration for therapy for multiple myeloma. 18 Earlier studies by other groups, including our laboratory, have shown that SCF-SKP2 ubiquitin proteasome pathway alterations in tumors is a ubiquitous phenomenon and is present in various tumors, such as CRC, ovarian carcinomas, and diffuse large Bcell lymphomas.…”
mentioning
confidence: 99%
“…It is this active site that can be targeted by some proteasome inhibitors (such as Bortezomib) (Figure 1) through nucleophilic attack (67,70). Additionally, the 19S regulatory particle (700 kDa) contains six ATPase and at least eight non-ATPase subunits, which are required for recognition, deubiquitination, unfolding, and translocation of tagged proteins prior to degradation by the 20S proteasome (71)(72).…”
Section: Ubiquitin-proteasome Pathwaymentioning
confidence: 99%
“…On the activation by E1 enzyme and the conjugation to E2 enzyme, ubiquitin moieties is transferred to the E3 ligase-recognized substrates, leading to polyubiquitination of the substrate protein, which will be destined for destruction by the 26S proteasome (Nandi et al, 2006;von Mikecz, 2006). The selectivity of the ubiquitinproteasome pathway for a particular substrate protein relies on E3 ligases.…”
Section: Introductionmentioning
confidence: 99%